2020
DOI: 10.1080/00438243.2019.1741439
|View full text |Cite
|
Sign up to set email alerts
|

‘Body-objects’ and personhood in the Iron and Viking Ages: processing, curating, and depositing skulls in domestic space

Abstract: This article explores practices of processing, displaying, and depositing human and animal crania in built environments and wetlands in the long Iron Age of Scandinavia. The paper first reports on a dataset of a range of practices targeting heads over the first millennium CE, with a particular focus on deposition of crania in built environments. I subsequently present a two-fold analysis of these data: an exploration of how reworking bodies into cranial objects transformed personhood in complex ways, and a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…As we have seen, many archaeological and anthropological discussions on the use of human skulls posit them as potent objects with only faint connotations to the persons to whom they once belonged (Bonogofsky 2011:4). The weight is instead put on discussing how crania and mandibles could be used by the living as aides in passage rites or as atmospheric interventions (Armit 2012:61;Eriksen 2020). In these examples, the skeletal remains are not to be directly equated with individuals, but sometimes seem to embody faint traces of the deceased person.…”
Section: Discussionmentioning
confidence: 99%
“…As we have seen, many archaeological and anthropological discussions on the use of human skulls posit them as potent objects with only faint connotations to the persons to whom they once belonged (Bonogofsky 2011:4). The weight is instead put on discussing how crania and mandibles could be used by the living as aides in passage rites or as atmospheric interventions (Armit 2012:61;Eriksen 2020). In these examples, the skeletal remains are not to be directly equated with individuals, but sometimes seem to embody faint traces of the deceased person.…”
Section: Discussionmentioning
confidence: 99%
“…Along with children, a wide array of 'body-objects' appears in depositional contexts: worked human bone (Fig. 2) and other selected body parts, some clearly products of violence (Eriksen 2020b).…”
Section: Ungrievable Bodiesmentioning
confidence: 99%
“…Along with children, a wide array of ‘body-objects’ appears in depositional contexts: worked human bone (Fig. 2) and other selected body parts, some clearly products of violence (Eriksen 2020b).
Figure 2.A human parietal bone perforated and inscribed with runes, from the excavations of Ribe, Denmark, dated to the eighth century.
…”
Section: Gender and More-than-human Worlds Of Iron And Viking Age Sca...mentioning
confidence: 99%
“…slaves), often hinges on dehumanizing them into states of non-agency—a common mechanism of oppression (Raffield 2018, 683). Furthermore, it is becoming widely recognized that being human was no guarantee to being universally perceived as a person in the Viking Age (Eriksen 2020; Lund 2017). Following such considerations of what creates social identity, it may be suggested that freedom, or the lack thereof, may be of more relevance to the configuration of personhood than, for example, gender.…”
Section: Willing Victims: Slave Girls As a Tropementioning
confidence: 99%
“…The Ballateare grave from Jurby on the Isle of Man is frequently cited in discussions of human sacrifice in the Viking Age (Fig. 4; Bersu & Wilson 1966; Eriksen 2020; Gardeła 2013; 2014; McLeod 2018; Price 2008; Symonds et al 2014; Wilson 2008). More importantly, it is often tied to Ibn Fadlan's narrative.…”
Section: Narratives Of Sacrifice and Archaeologymentioning
confidence: 99%